Tabel Periodik Kimia Berbasis Aplikasi Android - - AMIK BSI Bogor, Abdul Hamid; - AMIK BSI Jakarta, Rame Santoso; -STMIK Nusamandiri, Navy Apriyafiki Widanarko (IJNS - Indonesian Journal on Networking and Security, 2017)
Abstract – The development of Information and Communications Technology has changed the model and pattern of teaching in education. Especially the technological developments in the process of teaching and learning by using tools such as computers, smartphones and other. Chemical periodic table is a display of the chemical elements in the form of a table. The elements are arranged by electron structure so that the chemical properties of these elements vary regularly across the table. Each element is listed by its atomic number and chemical symbol. The periodic table also provides basic information about an element. By using the smartphone as a medium of learning it will be easier to get to know about the chemical elements, especially with the search function that allows users to search for a desired element and also the application is user friendly so the application is easy to use. Keywords: Elements, Chemistry, Android, Apps Abstrak – Perkembangan Teknologi Komunikasi dan Informasi telah mengubah model dan pola pembelajaran pada dunia pendidikan. Terutama perkembangan teknologi dalam proses pengajaran dan pembelajaran dengan menggunakan alat bantu seperti komputer, smartphone dan lain-lain. Tabel periodik kimia adalah tampilan unsur-unsur kimia dalam bentuk tabel. Unsur-unsur tersebut diatur berdasarkan struktur elektronnya sehingga sifat kimia unsur-unsur tersebut berubah-ubah secara teratur sepanjang tabel. Setiap unsur didaftarkan berdasarkan nomor atom dan lambang unsurnya. Tabel periodik juga memberikan informasi dasar mengenai suatu unsur. Dengan menggunakan smartphone sebagai media pembelajaran maka akan lebih mudah untuk mengenal tentang unsur-unsur kimia terutama dengan adanya fungsi pencarian sehingga memudahkan pengguna untuk mencari unsur yang diinginkan dan juga aplikasi ini user friendly sehingga aplikasi mudah di gunakan. Kata Kunci: Unsur, Kimia, Android, Aplikasi